1984
DOI: 10.1002/cne.902230406
|View full text |Cite
|
Sign up to set email alerts
|

The central projections of tooth pulp afferent neurons in the rat as determined by the transganglionic transport of horseradish peroxidase

Abstract: Transganglionic transport of horseradish peroxidase (HRP) or horseradish peroxidase-wheat germ agglutinin conjugate (HRP-WGA) was used to map in detail the central projections of trigeminal primary afferent neurons that innervate the dental pulp organ of the rat. In each of ten animals, 0.5-2.0 microliters of enzyme solution was injected into the pulp chamber of the first maxillary molar tooth. Postmortem examination of the decalcified teeth in all cases showed that the HRP/HRP-WGA remained confined to the pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(48 citation statements)
references
References 53 publications
1
45
1
Order By: Relevance
“…The dorsomedial nucleus, first described by Åstrøm (1953), can be distinguished from the rest of the Vo by its cytoarchitecture and is highly developed in rodents. The nucleus is known to receive trigeminal primary projection from exclusively intraoral structures (Arvidsson and Gobel, 1981;Marfurt, 1981;Jacquin et al, 1983;Marfurt and Turner, 1984;Shigenaga et al, 1986aShigenaga et al, ,b, 1989Takemura et al, 1987Takemura et al, , 1991. Prominent CGRP-and SP-ir projection of exclusively trigeminal primary neurons as shown in this study has added another characteristic that distinguishes the rodent dorsomedial nucleus from the rest of the BSTC.…”
Section: Cgrp-ir Primary Afferent Projection To the Rostral Subdivisimentioning
confidence: 74%
See 1 more Smart Citation
“…The dorsomedial nucleus, first described by Åstrøm (1953), can be distinguished from the rest of the Vo by its cytoarchitecture and is highly developed in rodents. The nucleus is known to receive trigeminal primary projection from exclusively intraoral structures (Arvidsson and Gobel, 1981;Marfurt, 1981;Jacquin et al, 1983;Marfurt and Turner, 1984;Shigenaga et al, 1986aShigenaga et al, ,b, 1989Takemura et al, 1987Takemura et al, , 1991. Prominent CGRP-and SP-ir projection of exclusively trigeminal primary neurons as shown in this study has added another characteristic that distinguishes the rodent dorsomedial nucleus from the rest of the BSTC.…”
Section: Cgrp-ir Primary Afferent Projection To the Rostral Subdivisimentioning
confidence: 74%
“…This suggests that a considerable proportion of the trigeminal primary nociceptive projection, especially from the intraoral structures, is directed to the relay nuclei located in the rostral subdivisions of the BSTC. This idea is supported by the fact that a large proportion of central projection of presumed primary nociceptors innvervating the tooth pulp is directed to rostral subdivisions of the BSTC (Arvidsson and Gobel, 1981;Westrum et al, 1981;Marfurt and Turner, 1984;Shigenaga et al, 1986bShigenaga et al, , 1989Takemura et al, 1991;Sugimoto and Takemura, 1993).…”
Section: Cgrp-ir Primary Afferent Projection To the Rostral Subdivisimentioning
confidence: 89%
“…Anatomic studies using transganglionic transport of neuronal tracers have shown that tooth afferents project to the principal sensory and spinal nuclei of the trigeminal system. 2 Accordingly, tooth movement in rats was seen to induce c-Fos expression in neurons localized in the rat trigeminal nucleus complex as revealed by Fos-immunoreactivity (Fos-IR). [3][4][5] It was also seen to activate neurons in the parabrachial nucleus, which is one of the important relay nuclei for processing information from the orofacial regions.…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with previous investigations of trigeminal projections to the brainstem. For example, Marfurt and Turner (1984) investigated tooth pulp afferents from the maxillary molar tooth in rats, and revealed projections that extended throughout the rostrocaudal extent of the TBNC, but were concentrated in the dorsal and medial portions of the nuclei. Our procedure differed from Marfurt and Turner's, in that our injection into the tooth was not confined to the pulp chamber.…”
Section: Discussionmentioning
confidence: 99%